Reconstructing Ecological Ethics in Madrasahs Through an Islamic Guidance and Counseling Approach from an Ecotheological Perspective - Asniti Karni; Kiki Septika Sari; Siti Muniroh; Wahyu Fitriana; Alia Mifta Hunni'mah; Natasya Maharani; Muzai Yanatul Arifah (Journal of Society Counseling, 2026)
The contemporary ecological crisis demands the strengthening ofzmoral and spiritual awareness through Islamic education. This study aims to reconstruct ecological morality in madrasas through an Islamic Guidance and Counseling approach supported by the Student Teams Achievement Divisions (STAD) cooperative learning model. The study used a qualitative field approach involving Guidance and Counseling teachers and students as research subjects. Data were collected through interviews, observations, and documentation, then analyzed using an interactive model and drawing conclusions and tested through triangulation of sources and techniques. Implementation was carried out by integrating reflective counseling services based on the values ​​of monotheism, trustworthiness, and ecological responsibility into STAD learning through heterogeneous groups, collaborative discussions, internalization of ecotheological values, and environmental project assignments. The results of the study indicate that the integration of an ecotheological perspective in Islamic Guidance and Counseling services through the STAD model effectively increases students' religious-ecological awareness, strengthens environmental responsibility, and fosters collaborative behavior in maintaining the sustainability of the madrasa environment. This research makes a practical contribution to the development of a systematic and sustainable ecological character development strategy in madrasas.